2017
DOI: 10.1159/000479156
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression Profile of Circular RNAs in the Serum of Patients with Diabetic Retinopathy Revealed by Microarray

Abstract: Purpose: Diabetic retinopathy (DR) is the leading cause of blindness among working age adults. Circular RNAs (circRNAs) are a kind of noncoding RNAs that are involved in the development of some diseases. Here, we aimed to determine the possible role of circRNAs in the pathogenesis of DR by determining the expression profile of circRNAs in the serum of DR patients. Methods: Nineteen subjects with type 2 diabetes mellitus with proliferative DR (T2DR), 15 subjects with type 2 diabetes mellitus without DR (T2DM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 32 publications
(31 reference statements)
0
40
1
Order By: Relevance
“…A limited number of papers have examined whether circRNAs may be present in serum, mostly using computational methods (Amorim et al., 2017; Gu et al., 2017; Wei et al., 2017). Here, we have used a combination approach and identified 133 extracellular circRNAs (ex‐circRNAs) and further validated age‐related changes in three different ex‐circRNAs: circ_1305 , circ_722, and circ_1445 .…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of papers have examined whether circRNAs may be present in serum, mostly using computational methods (Amorim et al., 2017; Gu et al., 2017; Wei et al., 2017). Here, we have used a combination approach and identified 133 extracellular circRNAs (ex‐circRNAs) and further validated age‐related changes in three different ex‐circRNAs: circ_1305 , circ_722, and circ_1445 .…”
Section: Discussionmentioning
confidence: 99%
“…The CDR1as/miR-7 pathway also plays a role in inducing cardiomyocyte apoptosis to promote showed the highest value as a therapeutic target in prediabetes and type 2 diabetes mellitus [43] . Through the study of sera from diabetic retinopathy patients via circular microarray, 30 circRNAs were observed to be markedly upregulated [44] . Subsequently, circ_0005015 was verified as being upregulated in the plasma, vitreous samples, and fibrovascular membranes of diabetic retinopathy patients and to facilitate retinal endothelial angiogenic function by targeting miR-519d-3p [45] .…”
Section: Circrnas In Cardiovascular Dis-easesmentioning
confidence: 99%
“…The role of circRNAs in the pathogenesis of DR has been investigated lately. Gu et al found that some circRNAs were significantly upregulated in the serum of patients with DR compared to that of controls and diabetes patients without retinopathy [63]. In another study, Zhang and colleagues identified circ_0005015 as the most significantly upregulated circRNA in plasma, vitreous samples, and fibrovascular membranes of diabetic retinopathy patients [64].…”
Section: Diabetic Retinopathymentioning
confidence: 99%